AN ANALYTICAL INVESTIGATION OF A MODIFIED STEFAN PROBLEM. - Yen,Yin-Chao; Tien,Chi (1966)
Approximate solutions of temperature distribution and melting rate of ice were obtained for the case where the mode of heat transfer is natural convection due to the thermal instability caused by the heated lower surface. Extensive numerical solutions were obtained for the ice-water system corresponding to various thermal conditions in terms of parameters defined as R sub delta T = (T sub s - T sub m)/ (T sub m - T 0) and phi = L/C sub p (T sub m - T 0), where T sub s is the temperature of the heat source, T sub m is melting point of ice, T sub 0 is the initial temperature of ice, L is the latent heat of fusion, and C sub p is heat capacity of ice. (Author)